A comparative study on estimation of critical buckling temperatures of single-walled carbon nanotubes - Guven, Ugur (ELSEVIER SCI LTD, 2016)
In this comparative study to estimate the values of critical buckling temperatures of carbon nanotubes, modelled as Timoshenko beam, two new nonlocal elasticity models based on Trefftz and Kounadis approaches are addressed. The previous results obtained from literature are compared with those obtained from two new models under simple boundary conditions. The comparative results reveal that the differences between critical buckling temperatures obtained from three nonlocal elasticity models is more pronounced,especially at the high modes and for the short nanotubes. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Nano-structures; Buckling; Thermomechanical; Analytical modelling; TIMOSHENKO BEAM; NANOBEAMS; MODEL; EQUATIONS; TORSION; COLUMN; Engineering; Materials Science